Der Wiederaufbau der nordamerikanischen Zivilisationslandschaft durch staatliche Maßnahmen, am Beispiel von Wisconsin - Gallusser, Werner A. (ERDKUNDE, 1978)
During the 19th century European settlers cleared Wisconsin's forests and oak-savannas, transforming them into the present-day cultural landscape. The land-use methods applied were, however, ill suited to the ecological needs of the land, and devastating erosion occured over the course of time. The federal government responded to the call for intervention by creating, in the 1930s, the Soil Conservation Service. A number of federal laws led to further activities of the SCS on water and resource conservation, recreation research, regional planning and ecological education. The present study at first demonstrates the dependence of the early SCS-measures on the physical situation of the area. It then presents the latest methods applied for overall areal reconstruction (for example minimum tillage, highway erosion control, and wildlife wetland habitat management). Two sample studies, of Buffalo County in western Wisconsin and of an individual farm show how the Agricultural Conservation Program and the Farm Conservation Plan respectively are put into practice. The guiding principle is a modern landscape in which the needs of the economy are balanced with the conditions of the natural environment.